The impact of student assessment on faculty members at Palestine Technical University - Khadouri from their point of view - Nassar, Ahmed Salim (Journal of Educational and Psychological Sciences, 2018)
The aim of this study was to identify the attitudes of the faculty members due to the students evaluation at the Palestine Technical University-Kadoorie.To achieve this objective, a questionnaire of three fields (relations, teaching, assessment) was prepared. The descriptive approach was used in the study. The number of faculty members was(96) males and females, they were selected in a stratified random sampling method. The results of the study showed that there were no statistically significant differences in the results of the average of the faculty members in the three fields of study due to the gender, years of experience, scientific qualification, and workplace variables at the level of significance (0.05). In light of the results, the researcher recommended to develop the necessary plans for the rehabilitation of the academic staff regarding teaching elements (teaching, assessment, classroom management) and supplying the academic staff with the feedback.